2019
DOI: 10.6008/cbpc2179-6858.2019.004.0013
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento do milho em resposta à rizobactérias, molibdênio e nitrogênio

Abstract: Bactérias como Azospirillum brasilense e Rhizobium tropici apresentam potencial para melhorar o desempenho agronômico do milho em função de sua atividade diazotrófica e, também por atuarem como rizobactérias promotoras do crescimento de plantas. Além disso, o uso destas espécies microbianas pode ampliar os benefícios isolados e combinados do molibdênio e nitrogênio aplicados por ocasião da semeadura. O objetivo deste trabalho foi avaliar os efeitos isolados e combinados de Azospirillum brasilense, Rhizobium tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
2
1
Order By: Relevance
“…The variety SCS 156 had lower plant height at the rate of 200 mL ha -1 , and the maize hybrid presented no significant difference for the rates tested. These are similar results to those of Picazevicz et al (2017) and Martins et al (2018), who found significant increases in the height of plants inoculated with A. brasilense. However, other studies reported that inoculation with A. brasilense does not increase plant height compared to plants without inoculation (Santini et al, 2018;Andrade et al, 2019;Souza et al, 2019;Silva et al, 2021).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The variety SCS 156 had lower plant height at the rate of 200 mL ha -1 , and the maize hybrid presented no significant difference for the rates tested. These are similar results to those of Picazevicz et al (2017) and Martins et al (2018), who found significant increases in the height of plants inoculated with A. brasilense. However, other studies reported that inoculation with A. brasilense does not increase plant height compared to plants without inoculation (Santini et al, 2018;Andrade et al, 2019;Souza et al, 2019;Silva et al, 2021).…”
Section: Resultssupporting
confidence: 91%
“…Nitrogen (N) is one of the most absorbed nutrients by maize; most of the maize N demand is supplied through synthetic fertilizers (Coelho & Resende, 2008). Therefore, many maize growers apply N rates from 30 to 120 kg ha -1 to meet the crop needs (Meira et al, 2009); however, expressive N losses may occur by leaching and volatilization, depending on the climate conditions, mainly when high N rates are applied (Picazevicz, 2017).…”
Section: Morfofisiológicas E Fotossintéticas De Materiais Genéticos D...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the seed inoculation with Azospirillum brasilense did not cause statistical differences in leaf N contents, which corroborates the results obtained by Picazevicz, Kusdra, and Moreno (2019). P concentration was higher in plants that received the inoculation treatment with Azospirillum brasilense (Table 7).…”
Section: Resultssupporting
confidence: 85%
“…(2020) and Debastiani (2016) found significant differences for maize PH and CIH, obtaining results that differed from those found in this study. Picazevicz (2017), working with maize in a greenhouse, mentioned that Azospirillum brasilense increases vegetative growth as a result of the release of phytohormones such as gibberellins, auxins and cytokinins-a finding that this study did not confirm.…”
Section: Resultscontrasting
confidence: 82%